The Lord is the Spirit : the Holy Spirit and the divine attributes - Gabriel, Andrew K. (James Clarke, 2012)
""The Lord is the Spirit"" (2 Cor 3:17) ... and yet one might be excused for thinking otherwise when reading studies on God's attributes-omnipotence, omniscience, omnipresence, immutability, impassibility, and the like. Although Christians throughout the ages have defended the deity of the Holy Spirit, theologians have not adequately taken the doctrine of the Holy Spirit into account when formulating a theology of the divine attributes. The resulting understandings of God fall short of being fully Trinitarian. Gabriel builds on contemporary Trinitarian theology by advocating for the integrat